Total Score Differences of Hospital Anxiety and Depression Scale – Depression (HADS-D) in Patients with Multidrug-Resistant Tuberculosis (MDR-TB) Based on Gender at H. Adam Malik General Hospital Medan - M. Surya Husada; Bahagia Loebis; Ariwan Selian (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Tuberculosis (TB) is a contagious and airborne disease. Over the decades, psychiatric morbidity in patients with MDR-TB has become increasingly recognized. Resistant tuberculosis is currently a serious health problem worldwide. This chronic disease takes a long time and causes various side effects, often causing symptoms of depression and anxiety in patients with Multidrug-resistant tuberculosis (MDR-TB) and pulmonary tuberculosis (TB). However, there are still relatively few who focus on psychiatric disorders in patients with MDR-TB. To find out the total score differences of Hospital Anxiety and Depression Scale - Depression (HADS-D) in patients with Multidrug-Resistant Tuberculosis (MDR-TB) based on gender. This study is an Unpaired Two Group Numerical Comparative Analytical study with a cross-sectional approach, namely by describing and analyzing a situation at a certain time using the Hospital Anxiety and Depression Scale - Depression (HADS-D) instrument. The results of the analysis with the Pearson test obtained a p-value <0.001 (p <0.05). There is a difference in the total score of Hospital Anxiety and Depression Scale - Depression (HADS-D) in patients with Multidrug-resistant tuberculosis (MDR-TB) based on gender at the H. Adam Malik General Hospital Medan.